Nurses’ views on and compliance with the guidelines of hand hygiene, including nail hygiene in a multi-profile hospital in Lesser Poland Province – the evidence for need of continuous education and training - Wałaszek, Marta; Jaślan, Dorota; Kołpa, Małgorzata; Wójowska-Mach, Jadwiga; Gniadek, Agnieszka; Różańska, Anna (Nursing in the 21st Century, 2021)
PERCEPTION AND PRACTICE Of HH AND NURSES EDUCATIONAL NEEDSAim. The aim of this study was to examine the current situation and potential needs for education aiming at improving Polish nurses’ views and attitudes in terms of compliance with hand hygiene guidelines.Material and methods. The study was based on a diagnostic survey method. A questionnaire based study and also visual evaluation of the nurses’ nails was carried out as well.Results. Our results reveal unsatisfactory nurses’ attitudes and compliance with the given area of hand hygiene recommendations. Especially, despite the nurses’ strong support for natural nails, in practice they did not always comply with the guidelines.Conclusions. It is necessary to develop and implement effective strategies of continuing education and training aiming at changing habits of healthcare workers, including nurses, in hand hygiene.